(untitled) (Perspectivas em Ciência da Informação, 2010)
Descriptive research using as bibliometric method the citation analysis to determine and evaluate the consumption of information in the journal Informação e Sociedade: estudos, enter the years of 2001-2005, using an amount of 1982 bibliographical references from the 103 articles, published between the years 2001 – 2005.